2018
DOI: 10.1002/hbm.24494
|View full text |Cite
|
Sign up to set email alerts
|

Acute tryptophan loading decreases functional connectivity between the default mode network and emotion‐related brain regions

Abstract: It has been shown that the functional architecture of the default mode network (DMN) can be affected by serotonergic challenges and these effects may provide insights on the neurobiological bases of depressive symptomatology. To deepen our understanding of this possible interplay, we used a double‐blind, randomized, cross‐over design, with a control condition and two interventions to decrease (tryptophan depletion) and increase (tryptophan loading) brain serotonin synthesis. Resting‐state fMRI from 85 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
(141 reference statements)
0
12
1
Order By: Relevance
“…Qualitative comparison with other monoaminergic drugs Our literature search yielded nine fMRI studies which investigated effects of levodopa [44,45], haloperidol [45], escitalopram [46], methylphenidate [47], d-amphetamine [48], bupropion [49], tryptophan depletion/loading [50], and citalopram [51]. One study reported decreased FC within ten of ten investigated networks after citalopram, but it was not reported whether these findings were significant [52].…”
Section: Influence Of Head Motion and Changes In Physiological Paramementioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative comparison with other monoaminergic drugs Our literature search yielded nine fMRI studies which investigated effects of levodopa [44,45], haloperidol [45], escitalopram [46], methylphenidate [47], d-amphetamine [48], bupropion [49], tryptophan depletion/loading [50], and citalopram [51]. One study reported decreased FC within ten of ten investigated networks after citalopram, but it was not reported whether these findings were significant [52].…”
Section: Influence Of Head Motion and Changes In Physiological Paramementioning
confidence: 99%
“…Impacts on neurotransmitter systems are shown using the same color scheme. This table refers to results in[4][5][6][44][45][46][47][48][49][50][51][52] and findings in this study.…”
mentioning
confidence: 96%
“…Procedure. The experiment and results described in this manuscript are part of a larger project that investigates the influence of 5-HT on several decision-making parameters and fMRI measures (Deza-Araujo et al, 2018;Neukam et al, 2018). For this study, we aimed for 100 homozygous subjects.…”
Section: Pharmacological Studymentioning
confidence: 99%
“…Although serotonin is best known for its role as a neurotransmitter, it plays an important role in mood, appetite, metabolism, vasoconstriction, and platelet function [81][82][83][84]. In our research, the level of serotonin was decreased.…”
Section: Discussionmentioning
confidence: 48%